Robust circuit and system design methodologies for nanometer-scale devices and single-electron transistors. - Schmid, A. (IEEE Transactions on VLSI systems)
In this paper, various circuit and system level design challenges for nanometer-scale devices and single-electron transistors are discussed, with an emphasis to the functional robustness and fault tolerance point of view. A set of general guidelines is identified for the design of very high-density digital systems using inherently unreliable and error-prone devices. The fundamental principles of a highly regular, redundant, and scalable design approach based on fixed-weight neural networks and multiple-valued logic are presented. It is demonstrated that the proposed design technique offers significantly improved immunity to permanent and transient faults occurring at the transistor level, and that it results in graceful degradation of circuit performance in response to device failures.